The state of Islam : culture and cold war politics in Pakistan - Saadia Toor (New York; Pluto Press, 2011)
Studies Pakistan through the lens of the Cold War and the War on Terror and sheds light on the processes behind the rise of militant Islam
Includes Reference &index
Keywords: Cold War; Islam Pakistan; Politics and government; Pakistan Politics and government